Reduction of SO2 to Elemental Sulfur in Flue Gas Using Copper-Alumina Catalysts - Seyyed Ebrahim Mousavi; Hassan Pahlavanzadeh; Reza Khalighi; Masoud Khani; Habib Ale Ebrahim; Saeed Abbasizadeh; Abbas Mozaffari (Journal of Nanotechnology)
This study aims to propose an advanced catalyst for the selective catalytic reduction of SO2, as a sustainable process to mitigate the emission of this toxic gas, which is a significant environmental concern. The conversion of SO2 through catalytic reduction with CH4 to elemental sulfur was investigated using Al2O3-Cu catalysts. The reaction was conducted under atmospheric pressure and at a temperature range of 550–800°C. A remarkable 99.9% SO2 conversion rate and 99.5% sulfur selectivity were achieved using the Al2O3-Cu (10%) catalyst at 750°C. The highest conversion rates of SO2 to elemental sulfur, with minimal production of undesirable by-products such as H2S and COS, were obtained when the SO2/CH4 molar feed ratio was set at 2, which is the stoichiometric ratio. Furthermore, the optimal catalyst exhibited excellent long-term stability for SO2 reduction with methane.